The Study of Extraction Methods and Characteristic of Red Fruit Oil (Pandanus conoideus LAM) - Guring Pohan, H; Arie Wardayanie, Ning Ima (Warta Industri Hasil Pertanian, 2006)
The study on the effect of oil extraction methods of red fruit using of amount water on the characteristic of red oil has been conducted.There were two methods used in this study,i.e:wet rendering using the water and dry rendering using the steam.In wet rendering the process was included a traditional process nd developed/modified of traditional process by using comparison between red fruit and water are1:2 anf 1:4;mean while dry rendering consist of blenders-steam-press and steam-blender-press.The result showed that the best treatment of oil extraction for red fruit were using the developed/modified of traditional process by using comparison between red fruit and water in 1:4 with have characteristic of red oil were followed :the yield of oil 4.61%,moisture content 3.54%,free fatty acid 2.96%,oleic acid 57.41%,beta-caroten 604.53 part per million (ppm) and a-tocoperol 416.82 ppm;mean while the best treatment for dry rendering (stem-blender-press)have resulted characteristic of red oil as follow :the yield oil 10.19%,moisture content2.14%,free fatty acid 2.84%,oleic acid 58.12%,beta-caroten 655.17 ppm and a-tocoperol 453.28 ppm.The result of analysis red oil not indicated content of trans fatty acid.